2007
DOI: 10.1007/s11249-006-9125-5
|View full text |Cite
|
Sign up to set email alerts
|

A multi-technique characterization of ZDDP antiwear films formed on Al (Si) alloy (A383) under various conditions

Abstract: The simulation of the lubrication of aluminum-silicon (Al-Si) alloy cylinder-bore conditions is an important goal in automotive tribology. This study describes the use of X-ray absorption near edge structure (XANES) to determine the macro-chemistry of zinc-dialkyl-dithiophosphates (ZDDPs) antiwear (AW) films formed on A383, an Al-Si alloy. The temperature dependence of the chemistry and mechanical properties were examined using X-ray photoelectron emission microscopy (X-PEEM), and imaging indentation technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 67 publications
5
45
1
Order By: Relevance
“…In Al-Si alloys, the ZDDP tribofilm is not effective in wear reduction as it is in Fe-based materials. This is also observed by Pereira et al [6] where it is suggested that this is due to the low tenacity of the film to the AlSi material. The reason for the low tenacity is because the Al-Si material can not provide thick oxide layer on the surface, therefore the ZDDP film is unable to bind to the surface via oxide as it does on the steel surface.…”
Section: Wear Scar Microstructure As a Function Of Rubbing Timesupporting
confidence: 76%
See 2 more Smart Citations
“…In Al-Si alloys, the ZDDP tribofilm is not effective in wear reduction as it is in Fe-based materials. This is also observed by Pereira et al [6] where it is suggested that this is due to the low tenacity of the film to the AlSi material. The reason for the low tenacity is because the Al-Si material can not provide thick oxide layer on the surface, therefore the ZDDP film is unable to bind to the surface via oxide as it does on the steel surface.…”
Section: Wear Scar Microstructure As a Function Of Rubbing Timesupporting
confidence: 76%
“…The study of Al-Si alloys against steel lubricated by commercial engine oils under boundary lubrication conditions has been reported occasionally since the 1960s and 1970s [2,3], with research focused mainly on the tribological performance of Al-Si alloys lubricated by zinc dialkyl dithiophosphate (ZDDP) [4][5][6]. The challenge in understanding fully these interactions lie mainly in the research being performed using different Al-Si alloys and under different testing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiwear additives are generally known to form protective tribofilms on the surface of contacting bodies. The most common such additive is zinc dialkyl dithiophosphate (ZDDP) [16], which can form tribofilms on various materials including steel, diamond-like carbon (DLC) and Si/Al alloys [17][18][19][20][21][22][23][24][25][26][27]. Though extensively studied, the specific processes involved in formation and removal of tribofilms in these different systems are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…11 summarise the results of surface characterisation for the Fe/Cu-system for both the steel ring and the CuPb22Sn2 disc. Results of elemental analysis (EDX) are expressed in mass percent.…”
mentioning
confidence: 99%